Identifying intersemiotic translation trends : a case study on Gaiman’s The graveyard book and its graphic novel translation - Ahnie, Kaylin Rose (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.